Limpet Tooth‐Inspired Painless Microneedles Fabricated by Magnetic Field‐Assisted 3D Printing. (7th October 2020) - Li, Xiangjia; Shan, Weitong; Yang, Yang; Joralmon, Dylan; Zhu, Yizhen; Chen, Yiyu; Yuan, Yuan; Xu, Han; Rong, Jiahui; Dai, Rui; Nian, Qiong; Chai, Yang; et al.
Abstract: Microneedle arrays show many advantages in drug delivery applications due to their convenience and reduced risk of infection. Compared to other microscale manufacturing methods, 3D printing easily overcomes challenges in the fabrication of microneedles with complex geometric shapes and multifunctional performance. However, due to material characteristics and limitations on printing capability, there are still bottlenecks to overcome for 3D printed microneedles to achieve the mechanical performance needed for various clinical applications. The hierarchical structures in limpet teeth, which are extraordinarily strong, result from aligned fibers of mineralized tissue and protein‐based polymer reinforced frameworks. These structures provide design inspiration for mechanically reinforced biomedical microneedles. Here, a bioinspired microneedle array is fabricated using magnetic field‐assisted 3D printing (MF‐3DP). Micro‐bundles of aligned iron oxide nanoparticles (aIOs) are encapsulated by polymer matrix during the printing process. A bioinspired 3D‐printed painless microneedle array is fabricated, and suitability of this microneedle patch for drug delivery during long‐term wear is demonstrated. The results reported here provide insights into how the geometrical morphology of microneedles can be optimized for the painless drug delivery in clinical trials. Abstract : Painless microneedles (MNs) inspired by limpet tooth with the capability of controllable drug delivery are produced via a magnetic field‐assisted 3D printing (MF‐3DP) process. The aligned magnetic nanoparticles show promising enhanced compression resistance. This opens intriguing perspectives for designing MNs with sharp features and high mechanical strength based on the bioinspired hierarchical structures in the 3D‐printed materials.